w(14+3)=w(25+2)

Simple and best practice solution for w(14+3)=w(25+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for w(14+3)=w(25+2) equation:


Simplifying
w(14 + 3) = w(25 + 2)

Combine like terms: 14 + 3 = 17
w(17) = w(25 + 2)

Reorder the terms for easier multiplication:
17w = w(25 + 2)

Combine like terms: 25 + 2 = 27
17w = w(27)

Reorder the terms for easier multiplication:
17w = 27w

Solving
17w = 27w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-27w' to each side of the equation.
17w + -27w = 27w + -27w

Combine like terms: 17w + -27w = -10w
-10w = 27w + -27w

Combine like terms: 27w + -27w = 0
-10w = 0

Divide each side by '-10'.
w = 0.0

Simplifying
w = 0.0

See similar equations:

| Y=cos(2*x) | | 3n+-11n+2=-18 | | y=10x+14 | | 8w+2w=-58 | | 8w+2w= | | x+2x=4x+10 | | 11y-6-3y^2=0 | | y=390+11(-2) | | 2xy(x+3)-z=2y-18 | | 1+1=2-3x | | Y=2500-240x | | 9-4(n-1)= | | -1-6x=-73 | | 7k-x+2(k+12)=52 | | 27=2x+3+4x+3+x+7 | | X^2-13*x+42=0 | | 13w=36+7w | | 3x^2-2x-190=0 | | 25-w=4w | | (3x+2)(5x+1)= | | 2x+8=2x-12 | | 8*x+9=48 | | 1a+2b+3c+4d+5e+6f+7g+8h+9i+10j+11k+12l+13m+14n+15o+16p+17q+18r+19s+20t+21u+22v+23w+24x+25y+26z= | | 3x-1=68 | | 9x+11=4x-(17-9x) | | =2.4 | | 28-3x-x^2=0 | | 6y-1=9k-4 | | 15r+7s+9r+7s= | | 2+7x=9x+5 | | 10. 15r+7s+9r+7s= | | 14x-2y+21x+7y= |

Equations solver categories